Analisis Pengaruh Citra Merek, Kualitas Produk Dan Kualitas Layanan Terhadap Minat Beli Sepeda Motor Honda (Studi Empiris pada mahasiswa FEB Universitas Muhammadiyah Surakarta) - Nalendraswati, Ariska Ayuningtias; Drs. Wiyadi, M.M., Ph.D., Drs. Wiyadi, M.M., Ph.D (2016)
This study uses a quantitative descriptive seeking cause - effect. In the results of this study will only see the effect of brand image, product quality, and the quality of services to the purchase intention of Honda motorcycles. Study used in this study were students FEB Muhammadiyah University of Surakarta. The sample used in this study was 100 respondents. This study is the analysis tool to test the validity and reliability of the data, the classical assumption test and multiple linear regression. In the process of testing using SPSS software. The results of the analysis is the brand image variable has a value sig. 0,000, variable quality of the product has value t sig. 0.006, and the variable quality of service mempunyia sig. 0,000 and the f test has sig. 0.000 smaller then 0.05 either partially or simultaneously variable quality of product and service quality significantly influence purchase intention of Honda motorcycles. Of the three variables that could explain the interest in buying a Honda motorcycle at 60.5% and there are other variables that influence it.